INDOOR AIR POLLUTION FROM BRIQUETTE-BURNING STOVES - SELINAWATI T.D. SELINAWATI; Retno damayanti; HERNI KHAERUNISA (Indonesian Mining Journal, 2006)
Recently, the use of coal briquette has already been socialized to substitute the role of oil and firewood in the household and small industries. In general the use of coal briquette burning stoves for household and small industries purposes is often conducted indoors, with inadequate ventilation. Yet knowledge of emissions from coal briquette burning stoves and how to evaluate emission and expo- sure levels are very limited and need to be developed. Study of indoor air pollution was undertaken to evaluate SO2, CO and NOx concentrations and its exposure potentials coming from the utilization of coal briquette for household and small industries purposes. Its results were compared to the charcoal burning process. To estimate the indoor concentration and exposure potential, the single-compart- ment mass balance model was used. Results show that the total amounts of hourly emitted SO2, CO and NOx for 1 kg coal briquette burning vary from 5.32-14.71 mg kg-1; 2.76-12.54 mg kg-1 and 112- 288 mg kg-1, respectively. While those emitted from charcoal burning are 0 mg kg-1, 6.79 mg kg-1 and 201 mg kg-1. The air exchange rate gives an effect to concentration level, peak indoor concentration and duration after the burning process. The hourly average concentrations of SO2, CO and NOx in the unventilated room are 22, 42 and 10 times, respectively higher than the used standards. While for charcoal burning, those were 0, 17 and 6 times, respectively.